2010
DOI: 10.3109/00365599.2010.533695
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of complex renal cysts: A critical evaluation of the Bosniak classification

Abstract: The main problem with the Bosniak classification is in separating category II and III lesions, which is of major importance, since decisions on intervention are based on this separation. The use of category IIF seems promising to detect those category II lesions that eventually will develop into malignancy and reduce overtreatment of lesions originally classified as category III. The scientific basis of this "new" classification strategy is, however, still missing. Data on other imaging modalities are too limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
1
48
1
3
Order By: Relevance
“…5 It was originally described using computed tomography (CT) imaging, but other modalities, such as magnetic resonance imaging (MRI), ultrasound (US), or contrastenhancement ultrasound (CEUS), are now being used to help better delineate these lesions. [6][7][8][9][10] The panel believes that if a complex cyst is first identified on US, contrast-enhanced axial imaging should be performed to better characterize the cyst. (Level of evidence: 4; Recommendation: D)…”
Section: Bosniak Classification -Introductionmentioning
confidence: 99%
“…5 It was originally described using computed tomography (CT) imaging, but other modalities, such as magnetic resonance imaging (MRI), ultrasound (US), or contrastenhancement ultrasound (CEUS), are now being used to help better delineate these lesions. [6][7][8][9][10] The panel believes that if a complex cyst is first identified on US, contrast-enhanced axial imaging should be performed to better characterize the cyst. (Level of evidence: 4; Recommendation: D)…”
Section: Bosniak Classification -Introductionmentioning
confidence: 99%
“…The original description proposed by Bosniak for 28 years ago is widely used nowadays with few changes, corroborating the relevance of a full command of the classification of these lesions by radiologists and urologists in their daily practices (3,12,13) .…”
mentioning
confidence: 62%
“…For this reason, the review article published by Muglia and Westphalen in the present issue of Radiologia Brasileira (17) is extremely important as the authors make a historical review of the main publications approaching the theme, with an overview of the classification in the current days, focusing on the most complex and controversial elements such as the differentiation of categories II, IIF and III (15) , the impact of the utilization of the category IIF on the clinical practice, and the follow-up of cysts IIF (8,10,13) . The article also approaches the utilization of other imaging methods (ultrasonography and magnetic resonance imaging) in comparison with computed tomography in the diagnosis and clinical management of these cysts (18) , besides indicating future and promising prospects with the use of intravenous contrast-enhanced ultrasonography (19) and diffusion-weighted magnetic resonance imaging.…”
mentioning
confidence: 99%
“…Since many category III lesions after surgery are found to be benign, a fifth category (IIF) was added, describing cystic masses that were not worrisome, but still required follow-up to verify stability over time and thereby ruling out malignancy 5. The addition of category IIF seems promising in detecting lesions that will eventually develop into malignancy,6 while lesions such as a CD over time typically remains unaltered, ruling out malignancy. These conclusions were supported by a recent study, which found that 15% of surgically resected renal tumours is actually benign 7…”
Section: Discussionmentioning
confidence: 99%